2014
DOI: 10.1111/1753-0407.12118
|View full text |Cite
|
Sign up to set email alerts
|

Association between magnesium concentration and HbA1c in children and adolescents with type 1 diabetes mellitus (儿童与青少年1型糖尿病患者的镁浓度与HbA1c之间的关系)

Abstract: The present study shows that low serum magnesium levels in children and adolescents with T1DM are associated with an increased risk of poor glycemic control, potentially contributing to the early development of cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 57 publications
9
23
2
Order By: Relevance
“…The evidence on the association of Mg concentrations with cardiometabolic risk factors is mainly limited to studies conducted in the adult population. A recent study revealed that low serum Mg levels increases the risk of poor glycemic control in children and adolescents with type 1 diabetes [30]. Our findings on the protective role of Mg against pediatric MetS and its components are consistent with this study conducted among diabetic children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…The evidence on the association of Mg concentrations with cardiometabolic risk factors is mainly limited to studies conducted in the adult population. A recent study revealed that low serum Mg levels increases the risk of poor glycemic control in children and adolescents with type 1 diabetes [30]. Our findings on the protective role of Mg against pediatric MetS and its components are consistent with this study conducted among diabetic children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetic children had significantly lower serum magnesium level compared to control children (1.83 ± .27 mg/dL in diabetic children versus 2.00 ± .16 mg/dL in control children). Taking cut off level of serum magnesium <1.7 mg/dL for definition of hypomagnesemia, [17] hypomagnesemia was detected in 28.2% of diabetic children compared to 9.9% of control children (Table 1). There were significant differences in lipid profile parameters between diabetic and control group with lower mean value of HDL in the diabetic group versus control group with P  < 0.01 and higher mean values of other lipid parameters in diabetic group versus control group with P  < 0.05 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence derived from clinical trials shows that oral magnesium supplements improve insulin sensitivity and dyslipidemia in diabetic and non-diabetic individuals [7,31,36]. Insulin resistance is inversely correlated with HDLcholesterol levels and atherogenic changes characterized by low HDL-cholesterol are mainly seen in insulin-resistant subjects [37].…”
Section: Discussionmentioning
confidence: 99%